(untitled) (American Journal of Islam and Society, 1997)
One of the main characteristics of contemporary Islamic thought, especially within the traditions of Islamic revival movements and the Islamization of knowledge movement, is its critical attitude toward both the Islamic heritage and western ideas, concepts, and theories. Thinkers and scholars of these movements have neither rejected entirely the western contributions toward knowledge, unlike the rejectionists, nor have they accepted it blindly, like the adoptationists. Most thinkers in these movements do not accept western ideas and concepts without a critical evaluation from an Islamic perspective. Khurshid Ahmad aptly remarks: The Islamic movement clearly differentiates between development and modernization on the one hand and westernization and secularization on the other. It says “yes” to modernization but “no” to blind westernization.’ Such a stance on modernization may not be attributed only to such Islamic movements as the Muslim Brotherhood of Egypt,2 established by Hasan al Banna,’ and the Jama‘at-e-Islami of the Indian subcontinent, founded by Abul A‘la Mawdudi,’ but also to the Islamization of knowledge movement.6 The type of modernization welcomed by scholars of these movements is not the same as that conceived by the West; rather, it is an Islamic modernization based on an Islamic epistemology ...